A RARE CONGENITAL CYANOTIC HEART DISEASE WITH PARAGANGLIOMA OF HEART- A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2011)
During autopsy, there is a real need to examine every vital organ and concentration may be given on some specific organ as per the history of the deceased. Such practice not only helps in determination of cause of death, but for properly investigating the case and in some extent helpful in academics. A, 22 years old unmarried female, complaints of chest pain was admitted and while on taking treatment expired. Autopsy was done and rare congenital anomaly of heart was detected .Further histopathological study showed presence of paraganglioma along with the malformation which is a relatively rare finding. Primary tumor of heart is very seldom occurrence and paraganglioma of heart is again less common among primary cardiac tumors.
Keywords: Autopsy; Congenital malformation of heart; Paraganglioma; Primary cardiac tumor